Schools for Social Justice: Experiences of Leadership in Two Costa Rican Educational Institutions - Cerdas-Montano, Virginia (2018)
Leadership for social justice is an issue that has gained relevance for professionals in education in many contexts around the world and Costa Rica is no exception. The objective of this study is the analysis around this theme, as well as the contribution of ideas both for practicing educators as well as those in training and for those who direct national educational policies. The interview protocol of the International Study of Leadership Development Network (ISLDN) and the Convention of the University Council for Educational Administration (UCEA) in the 2008 were used to interview two school administrators in a public preschool and a private multi-grade school. The results suggest a style of democratic and transformational leadership centered on aspects of social justice such as recognition and development of others’ capabilities. There were a number of similarities between the two cases related to four broad categories of social justice: economic, cultural, associative and developmental.